Pola Asuh Orangtua, Motivasi & Kedisiplinan dalam Meningkatkan Kesehatan Mental Remaja Papua - Alva Cherry Mustamu; Nur Hafni Hasim; Furaida Khasanah (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2020)
The mental condition of adolescents and children in Papua is currently worrying. They are vulnerable to various problems at the developmental stage such as mental and emotional problems related to emotional disorders, depression, resistance and behavioral disorders. the behavior or actions that arise by each individual depends on the emotional and thought conditions that arise before they decide to do something. The research is a descriptive analytic study with cross-sectional design aimed to determine the conditions that affect mental health in 80 teenage students of SMK Negeri 1 Sorong. The measuring instrument used was a questionnaire. simple logistic regression analysis test results show that parenting style, motivation and discipline simultaneously have an effect on adolescent mental health with a significance value (0,000 <0.005). Discipline, learning motivation has an influence on adolescent mental health with a significance value (0,000 <0.005) but parenting does not affect adolescent mental health with a significance value (0.382> 0.005).Â  Adolescents need support including the environment to prevent mental disorders because it has a close relationship with academic success.Â Keywords: Parenting style, Motivation, Dicipline, Mental health, Adolescents